2020
DOI: 10.1016/j.ccell.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Multi-phenotype CRISPR-Cas9 Screen Identifies p38 Kinase as a Target for Adoptive Immunotherapies

Abstract: Highlights d Expansion, memory, and oxidative and genomic stress define effective anti-tumor T cells d Multi-phenotype CRISPR-Cas9 screen reveals functional role of TCR-driven kinases d p38 regulates memory, redox homeostasis, and anti-tumor function of T cells d p38 is established as a target for improving TCR and CAR adoptive T cell therapies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 52 publications
10
101
0
Order By: Relevance
“…229 Loss-of-function studies in T cells have identified genes that, when deleted, can enhance T-cell responses, [230][231][232][233][234] such as p38 MAPK (MAPK14). 235 Many groups are also investigating whether candidate transcription factors, such as c-Jun, 236 or synthetic cell receptors, 237,238 such as the IL-2 receptor, 239 can be overexpressed to reprogramme T cells, prevent exhaustion, or convert suppressive extracellular signals into activating signals. A first-in-human Phase 1 clinical trial of multiplex CRISPR-Cas9 gene editing in T cells from three patients with advanced, refractory cancer (two patients with myeloma and one with sarcoma) demonstrated that this approach is safe and feasible.…”
Section: Ex Vivo Drug Modulation Modifications Of Culturing Conditionmentioning
confidence: 99%
“…229 Loss-of-function studies in T cells have identified genes that, when deleted, can enhance T-cell responses, [230][231][232][233][234] such as p38 MAPK (MAPK14). 235 Many groups are also investigating whether candidate transcription factors, such as c-Jun, 236 or synthetic cell receptors, 237,238 such as the IL-2 receptor, 239 can be overexpressed to reprogramme T cells, prevent exhaustion, or convert suppressive extracellular signals into activating signals. A first-in-human Phase 1 clinical trial of multiplex CRISPR-Cas9 gene editing in T cells from three patients with advanced, refractory cancer (two patients with myeloma and one with sarcoma) demonstrated that this approach is safe and feasible.…”
Section: Ex Vivo Drug Modulation Modifications Of Culturing Conditionmentioning
confidence: 99%
“…Another clue as to how blocking signaling cascades may overlap to improve T cell therapies was recently identified by the Restifo group ( 155 ). They used a multi-phenotype CRISPR screen to identify more than 25 targets downstream of T cell activation.…”
Section: Modulating Metabolism To Enhance Adoptive T Cell Therapymentioning
confidence: 99%
“…They used a multi-phenotype CRISPR screen to identify more than 25 targets downstream of T cell activation. They identified the stress response p38 MAP kinase as a key driver involved in preventing T cell mediated tumor immunity ( 155 ). This finding reinforces previous studies that elegantly demonstrated that ER stress, a target regulated by p38, impairs intratumoral T cell protein translation of cytotoxic molecules and regulates mitochondrial and T cell exhaustion ( 156 159 ).…”
Section: Modulating Metabolism To Enhance Adoptive T Cell Therapymentioning
confidence: 99%
“…Both pathways will inhibit cyclin dependent kinase 4 (CDK4) and CDK6 to maintain the retinoblastoma (RB) protein hypo-phosphorylated, preventing cell cycle transition from G1 to S phase, leading to senescence [36][37][38][39][40]. In addition, telomere-independent, DNA damage-associated cellular senescence has also been linked to p38 mitogen-activated protein kinase (p38MAPK) signaling in activated T cells [41,42].…”
Section: Senescencementioning
confidence: 99%
“…Furthermore, senescent T lymphocytes become able to suppress proliferation of normal T cells and promote tumor immune evasion [164]. In anti-CD3 + IL-2 stimulated T cells, inhibition of p38MAPK signaling proved to be helpful to reverse the senescence phenotype of CD8+ T cells by increasing their proliferation and functionality [41,42].…”
Section: Tumor-infiltrating Lymphocytesmentioning
confidence: 99%